Construction of a map-based reference genome sequence for barley, Hordeum vulgare L - Beier, S.; Himmelbach, A.; Colmsee, C.; Zhang, X. Q.; Barrero, R. A.; Zhang, Q. S.; Li, L.; Bayer, M.; Bolser, D.; Taudien, S.; Groth, M.; Felder, M.; et al. (My University, 2017)
Barley (Hordeum vulgare L.) is a cereal grass mainly used as animal fodder and raw material for the malting industry. The map-based reference genome sequence of barley cv. `Morex' was constructed by the International Barley Genome Sequencing Consortium (IBSC) using hierarchical shotgun sequencing. Here, we report the experimental and computational procedures to (i) sequence and assemble more than 80,000 bacterial artificial chromosome (BAC) clones along the minimum tiling path of a genome-wide physical map, (ii) find and validate overlaps between adjacent BACs, (iii) construct 4,265 non-redundant sequence scaffolds representing clusters of overlapping BACs, and (iv) order and orient these BAC clusters along the seven barley chromosomes using positional information provided by dense genetic maps, an optical map and chromosome conformation capture sequencing (Hi-C). Integrative access to these sequence and mapping resources is provided by the barley genome explorer (BARLEX).
Citation: Beier, S., Himmelbach, A., Colmsee, C., Zhang, X. Q., Barrero, R. A., Zhang, Q. S., . . . Mascher, M. (2017). Construction of a map-based reference genome sequence for barley, Hordeum vulgare L. Scientific Data, 4, 24. doi:10.1038/sdata.2017.44
Keywords: Bacterial Artificial Chromosomes; Physical Map; Libraries; Generation; Assemblies; Framework